Ifdil perceptual light technique (IPLT) an alternative brief approach for the reduction of trauma, phobia and psychological problems - Ifdil Ifdil; Nilma Zola; Rima Pratiwi Fadli (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Psychological problems continue to develop with the incessant occurrence of revolutionary fluctuations. However, the problem is more complex, with a continuous increase in growth rate not balanced with the psychological approaches and counseling related to recovery. In addition, several previous approaches require a relatively longer alleviation time. Therefore, Ifdil Perceptual Light Technique (IPLT) comes with a combination of technology, programming languages, and several previous approaches, which aim to reduce trauma, phobias and other psychological disorders in less than ten minutes. IPLT works by utilizing and combining light technology with programming languages to modify, change sensory and perceptual stimuli. It has IPLTC procedures namely Insight (I) Processing of Building Rapport (P), Lighting Techniques (L) Tools and Techniques (T), Closing and Follow Up (C). Based on trials, IPLT is very effective in reducing trauma, phobias and other psychological disorders. However, it requires broader development and testing with diverse samples for proper optimization of approaches.